Canadian Association of Gastroenterology (CAG) Position Statement on the Use of Hyoscine-n-butylbromide (Buscopan) During Gastrointestinal Endoscopy. Issue 6 (12th October 2021) - Forbes, Nauzer; Frehlich, Levi; Borgaonkar, Mark; Leontiadis, Grigorios I; Tse, Frances
Abstract: Hyoscine butylbromide, also known as hyoscyamine or scopolamine, and sold under the trade name Buscopan, is an antimuscarinic agent commonly used to induce smooth muscle relaxation and reduce spasmodic activity of the gastrointestinal (GI) tract during endoscopic procedures. However, the balance between desirable and undesirable (adverse) effects is not clear when used during GI endoscopy. The Clinical Affairs Committee of the Canadian Association of Gastroenterology (CAG) conducted systematic reviews and applied the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach to develop recommendations for the use of Buscopan during GI endoscopy. To summarize, we recommend against the use of Buscopan before or during colonoscopy ( strong recommendation, high certainty of evidence ). We suggest against the use of Buscopan before or during gastroscopy ( conditional recommendation, very low certainty of evidence ). We suggest the use of Buscopan before or during ERCP ( conditional recommendation, very low certainty of evidence ). More research is needed to determine whether patients undergoing advanced procedures such as endoscopic mucosal resection or endoscopic submucosal dissection benefit from its use. Buscopan should be used with caution in patients with cardiac comorbidities. According to its product monograph, Buscopan is contraindicated in patients with tachycardia, angina, and cardiac failure. Thus, Buscopan should be used very cautiously in patients with these conditions, and only when the potential benefits of its use outweigh the potential risks in a particular case. Such patients require careful cardiac monitoring in an environment where resuscitation equipment and appropriately trained staff to use it are readily available. According to its product monograph, Buscopan is also contraindicated in patients with prostatic hypertrophy with urinary retention, and therefore, should be used very cautiously in such patients as well, and only when the potential benefits of its use outweigh the potential risks in a particular case. Obtaining a preprocedural history of glaucoma is unlikely to be of value when considering Buscopan use. However, in cases where Buscopan has been used, patients should be counselled postprocedurally and told to present to an emergency facility should they experience eye pain, redness, decreased vision, nausea and vomiting or headache.